Belle and the Castle Puppy - Walt Disney Enterprises (Disney Princess Classic Library., 2012)
"All Rapunzel wants for her birthday is to see the floating lights, but to do that she's going to need the help of Flynn and Maximus. There's just one problem: the two do not get along. Can Rapunzel help these two enemies become friends before the trio gets into real trouble?"--Back cover.